mu-crystallin is a mammalian homologue of Agrobacterium ornithine cyclodeaminase and is expressed in human retina. - Kim, R Y (1992)
mu-Crystallin is the major component of the eye lens in several Australian marsupials. The complete sequence of kangaroo mu-crystallin has now been obtained by cDNA cloning. The predicted amino acid sequence shows similarity with ornithine cyclodeaminases encoded by the tumor-inducing (Ti) plasmids of Agrobacterium tumefaciens. Until now, neither ornithine cyclodeaminase nor any structurally related enzymes have been observed in eukaryotes. RNA analysis of kangaroo tissues shows that mu-crystallin is expressed at high abundance in lens, but outside the lens mu-crystallin is preferentially expressed in neural tissues, retina, and brain. An almost full-length cDNA for mu-crystallin was cloned from human retina. In human tissues, mu-crystallin mRNA is present in neural tissue, muscle, and kidney. This pattern of expression and relationship to an enzyme involved in unusual amino acid metabolism suggests the interesting possibility that mammalian mu-crystallins could be enzymes participating in processes such as osmoregulation or the metabolism of excitatory amino acids.